Nonlinear performance of nems: a resonant mass spectrometry - Mai Duc Dai; Chang-Wan Kim (Journal of Technical Education Science, 2014)
Nano-Electro-Mechanical Systems (NEMS) have recently allowed the in vitro molecular recognition. Most the detection, so far, is based on the harmonic oscillation regime, albeit nano mechanical resonators can easily reach the nonlinear vibrations. In this work, we have studied the nonlinear performance of carbon nanotube (CNT)-based NEMS for mass sensors using a continuum elastic model such as a beam model. It has been found that the nonlinear oscillation can significantly amplify the frequency shift of a CNT resonator due to mass adsorption, and consequently, the detection sensitivity of a resonator. Our study highlights the nonlinear oscillation for design and optimization of CNT-based NEMS mass spectrometry